Evaluating the performance of Moroccan social incubators: an SFA analysis of youth platforms under the national initiative for human development - Younes El Maaqili; Mariam Tlemcani Mhandez; Abdessamad Ouchen (Business, Management and Economics Engineering)
Purpose – This study focuses on the evaluation of youth platforms as an important  social incubator of the National Initiative for Human Development (NIHD) in Morocco, particularly to promote social entrepreneurship and support very small enterprises (VSE). Numerous social incubators have been created to support social entrepreneurship and foster innovative and effective socio-economic relations. However, their impact remains limited, raising  questions about their performance.